THE ORLEANS EPISODE OFMADEMOISELLE DE MONTPENSIER’SMEMOIRS AND THE IDEAL OF HEROIC FEMINISM - Svetlana Yu. Pavlova (Studia Litterarum)
The paper examines the influence of heroic feminism on the construction of the autobio- The paper examines the influence of heroic feminism on the construction of the autobiographical subject in the Memoirs by Mademoiselle de Montpensier (1627–1693), specifically in its Orleans episode. This episode is important as takes place in the central city of the author’s hereditary estate. During the Fronde des Nobles, haven confirmed her power over the city of Orleans, Mademoiselle tried to demonstrate that the nobles were the King’s true support and that she was in opposition to Cardinal Mazarin. The article analyzes the way the narrator’s actions in the city are described in the Memoirs in the light of the concept of Jeanne d’Arc as the greatest champion of French national interest, promoted in historiography, drama (Vernulz, d’Aubignac etc.), and fiction (Beroalde de Verville). Two aspects of Jeanne’s image, established by the mid-17th century, become most important in the Orleans episode of the Memoirs: her heroic service to France and God’s miracle manifested in her deeds. Jeanne d’Arc thus becomes part of a wider cultural context related to the tradition of heroic feminism that may be traced back to the Ancient Greek goddess Athena and manifests itself most fully in the image of “femmes fortes,” both historical and fictional (cf.: amazons in Ariosto, Tasso or Corneille’s female characters). The comparison of the narrator of the Memoirs with these images demonstrates that a peculiar ambience of the court and salon culture of the period that was apt to glorify exceptional heroic women enabled the memoirist to describe her entry to Orleans as triumphant episode of her life and in accordance with sublime understanding of her higher mission. Mademoiselle pictures herself as a courageous Princess worthy of Bourbon’s fame guided by Providence and loved by the people.